Seroprevalence of influenza A H1N1 and influenza D viruses in ruminants in Qatar - Hadeel T., Zedan (2025)
BackgroundInfluenza is among the most common viruses affecting humans and many animals worldwide. While influenza A (IAV) and D (IDV) viruses are associated with respiratory disease in humans and animals, respectively, their prevalence in the Middle East is unknown. MethodsHere, we assessed the seroprevalence of IDV and IAV/H1N1 in 331 ruminants (including camels, sheep, cattle, and goats) in Qatar. Sera samples were collected from ruminants in different farms and titrated by hemagglutination inhibition (HAI) assay. ResultsWe showed a high prevalence of IDV in all ruminants, ranging between 55 and 84 %, with the highest rates seen in sheep and cattle. The rates were much lower for IAV, ranging between 6 and 8 %, but were not detectable in goats. HAI titers of IDV-seropositive samples ranged between 20 and 2560, whereas IAV titers ranged between 20 and 640. ConclusionsOur study provides the first serological evidence of IDV and IAV/H1N1 in ruminants in Qatar. These results underscore the need for further investigation into the role of ruminants in influenza virus transmission.